Clinico-bacteriological study of diabetic foot: an observational study - Chhari, Akash Singh; Sharma, Priyank; Singh, Ashish Pratap; Shukla, Dhanwantri; Garg, Rishi; Gaharwar, APS (International Surgery Journal, 2016)
Background:Diabetic foot is the most important surgical manifestation of diabetes. With foot infection a major cause of morbidity bacterial infection play an important role in diabetic foot ulcers. Aim of this study was proposed to establish the bacterial profile and anti-microbial pattern of ulcer in an attempt to evaluate the role of infection in the foot lesions of diabetic patient. Associated factors like incidence, age, sex, predisposing factors, duration of diabetes, ulcer grade, hospital stay, modes of treatment, antibiotics sensitivity and other outcomes were also evaluated. Methods: This is a Prospective cohort study. The patients were admitted in surgical ward as provisional diagnosed cases of diabetic foot, were subjected to investigations including blood sugar (fasting, P.P, random), renal function test, x-ray of affected foot, fundus examination, grading of ulcer and various modes of treatment was given. Gross examination and culture from ulcers were done. Study was done in 104 patients over 1 year period. Results:One hundred four patients with diabetic foot were evaluated. Incidence of diabetic foot was 1.26%. Majority of cases were from rural areas (82.7%). Newly diagnosed cases of diabetes at admission (22.11%), majority of cases culture was positive (94.1% of 85). Staphylococcus was the predominant organism (61.17%), there were patients who were not on any mode of treatment (29.8%). Conclusions:Staphylococcus aureus a gram positive cocci was the most common micro-organism grown on culture from the ulcer (61.17%), next common micro-organism was Klebsiella (16.47%) gram negative bacilli. Piperacillin and metronidazole were most commonly used antibiotics. Diabetes was controlled by human actrapid (human regular insulin) in majority of the patients. Majority belonging to rural areas (82.7%). Most of the cases were relieved (77.88%). Only two cases fatality (1.92%) occurred during study period.